2012
DOI: 10.1186/1476-511x-11-137
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hemostatic genes expressed in human and rat leg muscles and a novel gene (LPP1/PAP2A) suppressed during prolonged physical inactivity (sitting)

Abstract: BackgroundPartly because of functional genomics, there has been a major paradigm shift from solely thinking of skeletal muscle as contractile machinery to an understanding that it can have roles in paracrine and endocrine functions. Physical inactivity is an established risk factor for some blood clotting disorders. The effects of inactivity during sitting are most alarming when a person develops the enigmatic condition in the legs called deep venous thrombosis (DVT) or “coach syndrome,” caused in part by musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…This notion is supported in a review of several studies by Hamilton et al [29], who demonstrated that the expression of some genes important for preventing diabetes and other metabolic risks is resistant to being restored after 12 h of inactivity, while the expression of others is not. In particular, a study examining the activity of lipid phosphate phosphatase-1 (LPP1) suggested that gene expression may be suppressed in response to chronic sitting despite participation in 1 h/day of vigorous exercise [30].…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported in a review of several studies by Hamilton et al [29], who demonstrated that the expression of some genes important for preventing diabetes and other metabolic risks is resistant to being restored after 12 h of inactivity, while the expression of others is not. In particular, a study examining the activity of lipid phosphate phosphatase-1 (LPP1) suggested that gene expression may be suppressed in response to chronic sitting despite participation in 1 h/day of vigorous exercise [30].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, passive cycling increases EE more than other commonly proposed sitting interventions like standing or sitting on an exercise ball (3). Furthermore, muscle activity is associated with changes to other cardiometabolic risk factors like HDL and triglycerides (30), lipoprotein lipase (7), and genes involved with overall homeostasis (38). It is possible that passive cycling may lower these other cardiometabolic risk factors and help to further counteract the deleterious effects of sitting; something that should be examined in longer term follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…Breaking up the workstation sitting by 2 min of walking at ~2mph three times an hour reduced the development of blood factors that promote pro-coagulation and the risk of thrombosis (Howard et al 2013). A case study of one individual and analyses of the animal tissue showed that subsequent bouts of physical activity did not reverse the suppression of lipid phosphate phosphatase-1, which would have a protective effect by degrading factors that promote thrombosis (Zderic and Hamilton 2012). This again suggests that intermittent activity to break up prolonged sitting is important, in this case to prevent hemostasis and risks of thrombosis.…”
Section: Worktationsmentioning
confidence: 99%
“…More commonly thought of as a health concern for elderly and those doing prolonged air travel, the case study of a 32-y old male who spent extensive time motionless at a computer station brought the issue to light (Beasley, Raymond, Hill, Nowitz, & Hughes, 2003). Subsequent experimental research identified hematopoetic changes and the expression of skeletal muscle genes that could contribute to the development of thrombosis as a result of physical inactivity brought on by prolonged sitting or simulation of prolonged sitting (Howard et al 2013;Zderic and Hamilton 2012). Breaking up the workstation sitting by 2 min of walking at ~2mph three times an hour reduced the development of blood factors that promote pro-coagulation and the risk of thrombosis (Howard et al 2013).…”
Section: Worktationsmentioning
confidence: 99%